American Sport and the Sports Heroes of the Roaring Twenties - Mazurkiewicz, Michał (Respectus Philologicus, 2014)
The aim of the article is to show the role of sport in American society against the background of a very important—for many reasons—period of great social transformation in the United States, one which visibly gathered pace in the 1920s. The author presents different aspects of popular culture, which was in full bloom on account of the following factors: the joy after World War I, a sense of optimism, the development of the economy and industry, the growth of big cities, and the greater affluence of the citizens. The analysis of that unusual decade corroborates the role of sport and its great power of influence on society. In an age when technology and mass production had robbed experiences and objects of their uniqueness, sports provided some of the unpredictability and drama that people craved when looking for romance and adventure. The reasons for the popularity of sport in the USA are presented, as well as the major sports diciplines and heroes of American sport who, in a time when mass production seemed to be making individuals less significant, met with a favorable response — people clung to the heroic personalities of sports figures. The analysis of the beginnings of professionalism in sport, the beginnings of organized support, and sports broadcasting, leaves no doubt as to the significance of the period. As the article demonstrates, it was a time of rapid and profound transformation in the realm of sport. Every serious examination of phenomena in contemporary American sport—and this is also true in the case of other countries—without a knowledge of the specificity of sport in the 1920s, would be far from perfect.